γ-Lindane Increases Microcystin Synthesis in Microcystis aeruginosa PCC7806 - Laura Ceballos-Laita; Laura Calvo-Begueria; Jessica Lahoz; María-Teresa Bes; María F. Fillat; María-Luisa Peleato (Marine Drugs, 2015)
HCH factories, and the waste dumpsites associated to its production, have become a global environmental concern, and their runoff could pollute ground and surface waters with high levels of the pollutant. In this study, the influence of lindane (γ-HCH) on microcystin production has been investigated in Microcystis aeruginosa PCC7806. This toxic cyanobacterium is highly tolerant to γ-lindane (20 mg/L), and produces more toxin (microcystin) in the presence of the pollutant. Microcystis degrades γ-lindane and presence of γ-lindane induces genes involved in its own degradation (nirA). RT-PCRsq has been used to monitor changes in levels of transcripts encoded by the mcy operon (mcyD, mcyH and mcyJ), responsible for the microcystin synthesis machinery, as well as other genes involved in its transcriptional regulation, such as ntcA and fur family members. The presence of lindane in the culture media induces mcyD expression, as well as ntcA gene transcription, while other genes, such as mcyH, (putative ABC transporter), are downregulated. The amount of microcystin found in the cells and the culture media is higher when M. aeruginosa is treated with γ-lindane than in control cells. The results suggest that in a lindane polluted environment, Microcystis toxic strains may enhance their microcystin synthesis.